2016
DOI: 10.3892/ol.2016.4787
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory myofibroblastic tumor in the head of the pancreas with anorexia and vomiting in a 69-year-old man: A case report

Abstract: Abstract. Inflammatory myofibroblastic tumor (IMT) is a rare condition of unclear etiology that is commonly observed in the lung but rarely in the pancreas. WHO classified IMT as a potentially malignant or aggressive tumor. In the present report, the case of a 69-year-old male patient with an IMT in the head of the pancreas, who experienced anorexia, nausea and vomiting, is presented. The patient's clinical symptoms were nonspecific, and the imaging findings revealed a hypovascularized pancreatic mass with ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…2,5 An unusual case of chronic pancreatitis as a result of recurrent episodes of acute pancreatitis caused by an IMT in the pancreatic head has been described in a human, 14 suggesting tumor development over a long period of time. In humans, a low worldwide incidence (0.04-0.7%) of IMT of the pancreas has been reported, 6 with 60% located in the pancreatic head. Complete surgical excision is the preferred therapeutic option for this tumor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,5 An unusual case of chronic pancreatitis as a result of recurrent episodes of acute pancreatitis caused by an IMT in the pancreatic head has been described in a human, 14 suggesting tumor development over a long period of time. In humans, a low worldwide incidence (0.04-0.7%) of IMT of the pancreas has been reported, 6 with 60% located in the pancreatic head. Complete surgical excision is the preferred therapeutic option for this tumor.…”
mentioning
confidence: 99%
“…Given its nonspecific signs and imaging findings, definitive diagnosis of IMT is based on histologic evaluation, 6,15,16 although transendoscopic biopsies or intraoperative frozen sections do not usually provide enough tissue to obtain a conclusive histologic diagnosis. 6,14 Distinction of IMT from various soft tissue sarcomas and inflammatory processes may also be challenging, although the histologic features of a population of large spindle-shaped myofibroblastic cells with mild atypia, admixed with inflammatory cells and an irregular vascular network, are considered the hallmarks of IMT. 16,17 Diffuse expression of vimentin, associated with variable expression of myofibroblastic markers, especially α-SMA, represents the common IHC features of IMT reported in the human and veterinary literature.…”
mentioning
confidence: 99%
“…2 The incidence of IMTs is approximately 0.04-0.7%, and clinical data have shown that they have a 25% rate of local recurrence and up to a 5% rate of distant metastasis. 3 The symptoms of IMT are ambiguous and generally related to obstructive symptoms caused by the large-sized mass. 2 Additionally, when a mass is found in the pancreas, IMTs are most commonly mistaken for pancreatic cancer according to their clinical and radiological characteristics.…”
Section: Introductionmentioning
confidence: 99%
“… 2 The incidence of IMTs is approximately 0.04-0.7%, and clinical data have shown that they have a 25% rate of local recurrence and up to a 5% rate of distant metastasis. 3 …”
Section: Introductionmentioning
confidence: 99%
“…IMT features mimcs malignancy on UGI scopy and radiological imaging and hence surgical exploration and complete resection is required for diagnosis and treatment. 9 The confirmation for the diagnosis would be ALK antibodies, anaplastic lymphoma kinase. Surgical removal is the best choice.…”
Section: Introductionmentioning
confidence: 99%